2022
DOI: 10.3389/fcell.2022.790947
|View full text |Cite
|
Sign up to set email alerts
|

The Pan-Cancer Crosstalk Between the EFNA Family and Tumor Microenvironment for Prognosis and Immunotherapy of Gastric Cancer

Abstract: Background:EFNA1–5 have important physiological functions in regulating tumorigenesis and metastasis. However, correlating EFNA genes in the tumor immune microenvironment (TIME), and the prognosis of patients with gastric cancer remains to be determined.Methods: Using public databases, the expression of EFNA1-5 in pan-cancer and gastric cancer was comprehensively analyzed using UCSC Xena, the Oncomine dataset and UALCAN. We further completed survival analysis by Kaplan-Meier plotter to evaluate the prognosis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…Previous studies have shown that members of the ephrin family play an important role in the pattern of nervous system, vascular system assembly and angiogenesis [ 20 , 21 , 22 , 23 , 24 ]. EFNA4 has also been reported to be involved in the proliferation of oral squamous cell carcinoma, hepatocellular carcinoma and gastric cancer [ 25 , 26 , 27 ]. However, the functions and mechanisms of EFNA4 in lung cancer are still not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that members of the ephrin family play an important role in the pattern of nervous system, vascular system assembly and angiogenesis [ 20 , 21 , 22 , 23 , 24 ]. EFNA4 has also been reported to be involved in the proliferation of oral squamous cell carcinoma, hepatocellular carcinoma and gastric cancer [ 25 , 26 , 27 ]. However, the functions and mechanisms of EFNA4 in lung cancer are still not clear.…”
Section: Introductionmentioning
confidence: 99%
“…We validated that hyperthermia reduced EFNA4 expression in GEM-resistant cell lines. EFNA4 has been implicated as a tumor promoter in various malignancies, including lung cancer [ 32 ], gastric cancer [ 15 ], hepatocellular carcinoma [ 33 ], and breast and ovarian cancers [ 34 ]. In PAAD, EFNA4 has also been identified as an important prognostic factor associated with shortened patient survival [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Through transcriptome analysis utilizing hyperthermia-related datasets sourced from the GEO system ( https://www.ncbi.nlm.nih.gov/gds/ ), our investigation pinpointed ephrin A4 (EFNA4) as a prominent factor significantly influenced by hyperthermia in the context of cancer treatment. EFNA4, an important member of the ephrins family, has been intricately associated with both developmental processess and tumorigenesis [ 15 ]. Notably, previous research has implicated EFNA4 in the activation of the renown oncogenic protein β-catenin, thereby potentiating the malignant characteristics of hepatocellular carcinoma cells [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, tumor-infiltrating immune cell (TIIC) dysfunction in the TME of gastric cancer is vital for its development and progression [ 7 ]. TIICs such as tumor-infiltrating neutrophils (TINs), regulatory T cells, tumor-associated macrophages, and CD8 + T cells have been described as outcome indicators in multiple cancer types, including gastric cancer [ 5 , [8] , [9] , [10] , [11] ]. Targeting of TIICs has exhibited promise in regard to improving current immunotherapies [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%